Auto-gouvernement populaire et auto-détermination des manières de vivre - Jérôme Baschet (Terrains/Théories)
The Zapatista experience, which has been underway in Chiapas for more than 27 years, is one of the most remarkable "real utopias" that can be observed today. Although it participates in a general movement of relocalization of politics, of which communalism (or municipalism) is one of the expressions, we are dealing here with another historical and cultural horizon. It is under the name of autonomy that the Zapatista rebels synthesize their experience. This contribution describes the most remarkable characteristics of this experience, and analyzes its theoretical scope. It aims to outline the contours of politics without the State, by identifying the criteria that allows to differentiate non-state forms of politics from its State form; and this without dissociating the question of political organization from a broader perspective that engages the transformation of ways of living.